Environmental Assessment of Atmospheric Dioxin Dispersion from a Municipal Wastes Power Plant, Indonesia: Kajian lingkungan dispersi dioksin atmosfer dari pembangkit listrik tenaga sampah perkotaan, Indonesia. - Sulaiman, Albert; Dewanti, Dian Purwitasari (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
We assess of environemental effect of the dioxin dispersion from municipal waste power plant (MWPP) covering, characteristic of the dispersion and health risk affected communities in  Indonesia. The dispersion studies through modeling which is  done with the following steps 1 ) estimate dioxin emissions from incinerator processing, 2 ) design the dioxin dispersion by literature review, 3 ) calculate health risk of communities based on the dispersion modeling.  The results show that the dispersion of dioxin is represented in the form of a non-Gaussian solution of the advection-diffusion equation with taking into account the settling and deposition velocity. In the case of MWPP with capacity, 80 tonnes per day produce a concentration of 0.04 pg TEQ/Nm3 in residential areas which are located  200m from chimney. Inhalation exposure resulting is 5.28 pg 1-TEQ/( kg-day ) to adults and 6.95 pg 1-TEQ/( kg-day ) to children. The strategy took to adjust by WHO environmental quality standard  4 pg 1-TEQ /( kg-day ), we increase the reduction of APC  25%. The calculation of emissions based on combustion processes shows that the dioxin concentration of MWPP is still below the threshold required by WHO.